Rethinking of Curriculum for the Senior Staff Course of Bangladesh Public Administration Training Centre: An Empirical Analysis - Islam, Md Zohurul; Haque, Md Shafiqul; Mannan, Md Abdul (Journal of Management and Development Studies, 2014)
One of the mandates of Bangladesh Public Administration Training Centre (BPATC) is to develop human capital of senior level civil servants of Bangladesh. This study has identified the development needs of the Joint Secretaries of Bangladesh Civil Service in order to facilitate knowledge and skills through Senior Staff Course (SSC) organized by BPATC. This study has used quantitative research approach. Data were collected from different levels of respondents that include officers of the rank of Joint Secretary, Additional Secretary and Secretary. The results have yielded seven thematic areas, in respect of knowledge and skills where Joint Secretaries are required to develop and with these seven thematic areas course contents need to be developed to achieve present and future priorities of the Government of Bangladesh.